2012
DOI: 10.1073/pnas.1202882109
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Myc translocations are independent of chromosomal location and orientation of the immunoglobulin heavy chain locus

Abstract: Many tumors are characterized by recurrent translocations between a tissue-specific gene and a proto-oncogene. The juxtaposition of the Ig heavy chain gene and Myc in Burkitt’s lymphoma and in murine plasmacytoma is a classic example. Regulatory elements within the heavy chain constant region locus are required for Myc translocation and/or deregulation. However, many genes are regulated by cis-acting elements at distances up to 1,000 kb outside the locus. Such pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Indeed, recent large-scale studies have confirmed this, demonstrating that translocations tend to occur between sites that are spatially juxtaposed in the nucleus (Hakim et al, 2012;Zhang et al, 2012). Arguing in favor of movement, on the other hand, Spehalski et al (2012) showed that Myc-Igh translocations in mouse cells occur at the same frequency regardless of where the Igh is placed in the genome. Understanding what regulates DSB movement and its impact on specific recombination events is clearly important for understanding oncogenic translocations.…”
Section: Chromatin Movement Driven By Nucleosome Remodelingmentioning
confidence: 90%
“…Indeed, recent large-scale studies have confirmed this, demonstrating that translocations tend to occur between sites that are spatially juxtaposed in the nucleus (Hakim et al, 2012;Zhang et al, 2012). Arguing in favor of movement, on the other hand, Spehalski et al (2012) showed that Myc-Igh translocations in mouse cells occur at the same frequency regardless of where the Igh is placed in the genome. Understanding what regulates DSB movement and its impact on specific recombination events is clearly important for understanding oncogenic translocations.…”
Section: Chromatin Movement Driven By Nucleosome Remodelingmentioning
confidence: 90%
“…Cell lines bearing Myc translocations with either the ARS /Igh 11 transgene (schematics of the molecular structure of the transgene and Myc / Igh-TG translocations are presented on Supplementary Figure 6 ) or endogenous Igh [ 28 ] were transduced with Cre-ER-expressing or empty retroviral vectors (EV) [ 29 ]. 4-OHT treatment triggers nuclear translocation of Cre-ER and recombination of loxP sites in target DNA resulting in complete deletion of hs3a, hs1,2, hs3b and hs4 enhancers.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, transcription at the IGH@ locus is controlled by enhancers elements spread out as wide as 2.5 Mb of the locus [12], and it contains regulatory elements necessary not only for MYC activation but also the promotion of translocation [13]. CMA detected a 455 Kb copy number loss on chromosome band 14q32.2, not detected by FISH since the probe used was outside of this region.…”
Section: Discussionmentioning
confidence: 99%
“…The IGH transcription factory, about 2.5 Mb in size [12], localizes the regulatory elements for MYC deregulation and variable regions that promote translocation [13]. The IGH@ locus, is a hotspot for recombination and mutation of immunoglobulin genes during B-cell maturation, processes that usually promote translocations with oncogenic potential [11].…”
Section: Introductionmentioning
confidence: 99%